2007
DOI: 10.1242/jcs.03331
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of de novo ceramide synthesis upregulates phospholipase D and enhances myogenic differentiation

Abstract: In L6 skeletal myoblasts induced to differentiate by Arg8-vasopressin treatment, a short-lived lowering of ceramide levels was observed, followed by a long-lasting elevation that was prevented by inhibitors of the de novo synthesis pathway, fumonisin B1 and myriocin. Both inhibitors increased the expression of myogenic differentiation markers and cell fusion rate, whereas short-chain ceramides inhibited these responses. Similar drug effects were observed on primary mouse satellite cell differentiation. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 47 publications
(69 reference statements)
2
45
1
Order By: Relevance
“…It has been reported that PLD1 is involved in the AVPstimulated myogenic differentiation of L6 rat skeletal myoblasts (Komati et al, 2005;Naro et al, 1997), and that ceramide is a negative regulator in this process upstream of PLD1 (Mebarek et al, 2007). A potentially significant difference between our study and the previously reported ones is that the C2C12 satellite cells undergo differentiation upon growth factor deprivation, in the absence of any hormonal stimulation, which mirrors the myogenic process in normal muscle development and regeneration.…”
Section: Discussioncontrasting
confidence: 50%
“…It has been reported that PLD1 is involved in the AVPstimulated myogenic differentiation of L6 rat skeletal myoblasts (Komati et al, 2005;Naro et al, 1997), and that ceramide is a negative regulator in this process upstream of PLD1 (Mebarek et al, 2007). A potentially significant difference between our study and the previously reported ones is that the C2C12 satellite cells undergo differentiation upon growth factor deprivation, in the absence of any hormonal stimulation, which mirrors the myogenic process in normal muscle development and regeneration.…”
Section: Discussioncontrasting
confidence: 50%
“…Taking into consideration the emerging evidence of the roles played by SACs (9,43) and cytoskeletal remodeling in skeletal muscle differentiation (9,29), this mechanism of SAC activation may have profound implications in muscle development, regeneration, and diseases, underlying the need to understand the functions of the subplasmalemmal acto-myosin network and its ability to transmit tensional forces to the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The membrane-bound enzyme neutral sphingomyelinase 2 (nSMase2), encoded by the sphingomyelin phosphodiesterase 3 (Smpd3) gene, cleaves sphingomyelin to generate the lipid second messenger ceramide, which affects a variety of cellular process, including proliferation, apoptosis, and differentiation (31)(32)(33)(34). A deletion mutation in the Smpd3 gene was identified in fragilitas ossium (fro), a mouse model of osteogenesis imperfecta (35).…”
Section: Although Bone Morphogenic Protein (Bmp) Signaling Promotes Cmentioning
confidence: 99%